Experience of providing medical care for intracerebral hemorrhage in a participant of the 2018 FIFA World Cup - N. I. Makoveeva; I. A. Strel'nikova; G. Yu. Chernogaeva; R. S. Chernukha; A. S. Benyan (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2023)
Introduction. Holding mass sports events of international level imposes a special responsibility on the medical services of the host city. The issues of organizing medical support for competitions are one of the foundations for the safety of all participants. By identifying different client groups, the organizers provide optimal conditions for each of them, this also applies to medical support.Aim. To describe the features of medical support in a life-threatening condition to a representative of one of the client groups of the 2018 FIFA World Cup in Samara.Material and methods. A clinical case of stroke that occurred during the 2018 FIFA World Cup in Samara is presented. The stages and timing of the provision of assistance, the interaction between the links of the medical service, the coordination of medical support are described, and the other factors that played a role in the outcome of the patient's disease are also reflected.Results. The fastest possible diagnosis and medical support at the prehospital stage led to the delivery of the patient to an authorized hospital and access to specialized medical care within the time frame envisaged by clinical protocols and recommendations. The inpatient stage of treatment with the use of high-tech methods of surgery and intensive care ended in a complete recovery of the patient. Conclusion. The described clinical case illustrates the expediency of the special requirements put forward to the medical support of major sports competitions. Competent operational planning, training of medical staff and their equipment, built inter- and intradepartmental interactions ensure the availability and quality of medical care, including in life-threatening conditions.